PERAN PERGURUAN TINGGI DALAM MERUBAH PERSEPSI NEGATIF TERHADAP ISLAM DENGAN MUNCULNYA KELOMPOK RADIKALISME - Juni Erpida Nasution; Hendriadi (STAI Nurul Falah Airmolek, 2019)
Islam is a religion of peace, religion rahmatan lil'alamin, religion that is tolenration. But due to the emergence of schools, schools, it was only in the name of Islam in its radical actions. One of the trigger factors for the emergence of radicalism is the understanding of religion in extreme ways, which in turn raises the assumption that other parties who are not understanding are wrong and violence is a legitimate way to change the situation. As a result, many people, especially ordinary people who perceive that Islam is a religion that is not good, even people who adhere to the religion of Islam are said to be terrorists, this makes the belief in Islamic religion unstable. This problem is caused by the lack of understanding and insight of the people towards Islam which is really and the background of the coming of radicalism itself. Here universities play an important role as people who are intellectual, think critically and act concretely, to change negative perceptions of Islam with the emergence of radicalism groups.